Boredom Intervention Training Phase I: Increasing Boredom Knowledge through a Psychoeducational Video - Patti C. Parker (MDPI AG, 2021)
Boredom is a salient emotion experienced in postsecondary settings, and evidence reveals that it can negatively impact academic achievement and motivation. Drawing from the control-value theory (CVT) of achievement emotions (Pekrun, 2006) and the component process model of emotions (CPM; Scherer, 1984), our study examines the first phase of a multi-sequenced online boredom intervention training (BIT) program. The goal of Phase I of BIT was to increase university students’ (N = 85) knowledge about boredom as a scholarly construct. Students completed four components of the Phase I BIT session, including: (a) a baseline survey and knowledge quiz, (b) a psychoeducational video, (c) a consolidation exercise, and (d) a follow-up knowledge quiz. We employed a repeated measures analysis to measure changes in knowledge after students watched the psychoeducational boredom video. Our findings reveal that students became more knowledgeable about boredom, learned something novel, and were interested in the intervention. The results are discussed in terms of the implications for research, theory, and practice.